2018
DOI: 10.1039/c8mh00206a
|View full text |Cite
|
Sign up to set email alerts
|

Hard-magnetic cell microscaffolds from electroless coated 3D printed architectures

Abstract: We report the application of 3D printing and wet metallization to the fabrication of magnetically driven microscaffolds for cell delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…Among them, the use of a magnetic carrier system comprising biomaterial-based magnetic microcarriers to target the delivery of therapeutic agents (e.g., drug, cell, and both of them) has been studied by different research groups because magnetic fields enable minimally and non-invasive surgery via tissue penetration without its distortion (Figure S1, Supporting Information). [20][21][22][23][24][25][26] Ideally, the magnetic carrier system needs to satisfy four functions: 1) enhanced cell penetration and adhesion using scaffolds with three-dimensional (3D) porous structures, 2) loading of bioactive molecules into the scaffolds for cell stimulation, 3) biocompatibility and biodegradation of the scaffolds, and 4) precise delivery of therapeutic agent-loaded scaffolds to the target lesion using an external magnetic field generator. However, no system having all these functions has been reported among magnetic carrier systems developed so far.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, the use of a magnetic carrier system comprising biomaterial-based magnetic microcarriers to target the delivery of therapeutic agents (e.g., drug, cell, and both of them) has been studied by different research groups because magnetic fields enable minimally and non-invasive surgery via tissue penetration without its distortion (Figure S1, Supporting Information). [20][21][22][23][24][25][26] Ideally, the magnetic carrier system needs to satisfy four functions: 1) enhanced cell penetration and adhesion using scaffolds with three-dimensional (3D) porous structures, 2) loading of bioactive molecules into the scaffolds for cell stimulation, 3) biocompatibility and biodegradation of the scaffolds, and 4) precise delivery of therapeutic agent-loaded scaffolds to the target lesion using an external magnetic field generator. However, no system having all these functions has been reported among magnetic carrier systems developed so far.…”
Section: Introductionmentioning
confidence: 99%
“…The cell-loaded magnetic microcarriers have been developed for biomedical applications using magnetic guidance for targeted delivery to lesion sites (Figure S1, Supporting Information). [20][21][22][23][24][25] However, the body of most microcarriers is made of nonbiodegradable photoresist-based materials, and the magnetic response of microcarriers is imparted through coatings of metals such as cobalt and nickel, which can cause substantial acute toxicity. [20][21][22][23][24] More recently, a magnetic microcarrier composed of poly(lactic-co-glycolic acid) (PLGA) has been proposed for knee cartilage regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of smart autonomous micro‐ and nanomotors that propel themselves, navigate in complex media, and perform various functions is an exciting technological challenge . The self‐propulsion of these micro‐ and nanomachines can be achieved by the asymmetrical decomposition of a chemical/biochemical fuel on the motors surface or by external inputs such as light, ultrasound, electrical, or magnetic fields . Previous research has demonstrated the advantages of using these tiny self‐propelled micro‐ and nanoswimmers for biosensing, transportation and manipulation of biological samples, drug delivery, and assisted fertilization …”
Section: Introductionmentioning
confidence: 99%